Decarboxylation of Poly[N‐(acryloyloxy)phthalimide] as a Versatile Tool for Postpolymerization Modification. Issue 10 (7th April 2022) - Frech, Stefan; Molle, Edgar; Hub, Cornelius; Theato, Patrick
Abstract: Herein the decarboxylation of poly[ N ‐(acryloyloxy)phthalimide] (PAP) for the synthesis of functionalized polymers is reported. PAP homopolymer and block copolymers are used as precursor polymers for the straightforward functionalization via decarboxylation and subsequent Michael‐type addition or nitroxide radical coupling (NRC). Abstract : New functional polymers are synthesized via photochemical decarboxylation of poly[ N ‐(acryloyloxy)phthalimide bearing an active ester prone to single‐electron transfer. The secondary radical formed at the backbone in the decarboxylation process is readily used for various types of functionalization. First, Michael‐type addition is performed to create new polymeric structures. Second, 2, 2, 6, 6‐tetramethylpiperidin‐1‐yl)oxyl (TEMPO)‐functionalities are introduced which are utilized for grafting side chains.